The Central Role of Left Atrium in Heart Failure - Carpenito, Myriam; Fanti, Diego; Mega, Simona; Benfari, Giovanni; Bono, Maria Caterina; Rossi, Andrea; Ribichini, Flavio Luciano; Grigioni, Francesco (Frontiers in Cardiovascular Medicine, 2021)
In past cardiovascular medicine, the attention to the left ventricle-identified as the only indicator and determinant of healthy or unhealthy cardiac conditions- has systematically hidden the role of the left atrium (LA). The recent advances in cardiovascular imaging have provided a better understanding of LA anatomy, physiology, and pathology, making us realize that this functional structure is far from being an innocent spectator. We now know that the LA's mechanical and neuro-hormonal properties play a relevant part in several cardiovascular diseases, including atrial fibrillation, ischemic heart disease, valvular heart disease, and heart failure. The present review aims to describe the role of LA in the specific setting of heart failure. We provide currently available information on LA structure and function and summarize its role as a determinant of symptoms, prognosis, and potential therapeutic target in heart failure patients.